Visible Light Assisted Hantzsch Reaction: Synthesis of Polycyclic Dihydropyridines - Nadaf, Ankusab N.; Shivashankar, Kalegowda (Letters in Organic Chemistry, 2019)
The polycyclic dihydropyridine nucleus represents the heterocyclic system of invaluable core motifs with wide applications in chemical, biological and physical properties. Although this kind of compounds have been extensively synthesized by other groups, the synthesis of these compounds under CFL light intensity were not explored. The synthesis of polycyclic dihydropyridine derivatives were achieved through the reaction of 4-hydroxycoumarin, aromatic aldehydes and ammonium acetate under CFL light irradiation conditions. A series of polycyclic dihydropyridine derivatives were prepared under CFL light irradiation conditions with high yield, short reaction time, ambient condition and without the use of catalyst. The results displayed an efficient method for the synthesis of polycyclic dihydropyridine derivatives. Clean profile, short reaction time, low cost and use of CFL light intensity instead of catalyst making it a genuinely green protocol.
Keywords: CFL